Human papillomavirus 16 E6 modulates the expression of host microRNAs in cervical cancer - Wei Ben; Yang Yang; Jing Yuan; Jingxia Sun; Mingli Huang; Dandan Zhang; Jianhua Zheng (Elsevier, 2015)
Objective: Human papillomavirus (HPV) infection is a prerequisite of developing cervical cancer, approximately half of which are associated with HPV type 16. There are reports that HPV can disturb the expression pattern of host miRNAs, but its mechanism is not well understood. Materials and Methods: In this study, we scanned 11 tumorigenesis related miRNAs in Hela cells that were overexpressed with HPV type 16 E6 protein. Results: We found the expression of miR-21 was upregulated by HPV type 16 E6 protein and meanwhile, the expression of miR-27a and miR-218 was downregulated. Furthermore, we identified that miR-21 overexpression could promote Hela and U2OS cells proliferation by targeting phosphatase-tensin homolog (PTEN), the result of which can be rescued by miR-21 inhibitor. In addition, E6 overexpression could also promote Hela cell migration and invasion. Conclusion: Our results indicate that HPV infection and subsequent transformation take place through complex regulatory patterns of gene expression in the host cells, part of which are regulated by the E6 protein.